2018
DOI: 10.3390/mi9010037
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Mechanical Planarization and Old Italian Violins

Abstract: Previous studies have shown that spectral analysis based on force data can elucidate fundamental physical phenomena during chemical mechanical planarization (CMP). While it has not been literally described elsewhere, such analysis was partly motivated by modern violinmakers and physicists studying Old Italian violins, who were trying to discover spectral relations to sound quality. In this paper, we draw parallels between violins and CMP as far as functionality and spectral characteristics are concerned. Inspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 28 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…With the following equation, frequency becomes order (p). [28][29][30] The order is then the number of events or vibrations per revolution. Since we are normalizing to the speed of the platen, an order of one corresponds to the frequency from the platen.…”
Section: New Tribological Resultsmentioning
confidence: 99%
“…With the following equation, frequency becomes order (p). [28][29][30] The order is then the number of events or vibrations per revolution. Since we are normalizing to the speed of the platen, an order of one corresponds to the frequency from the platen.…”
Section: New Tribological Resultsmentioning
confidence: 99%
“…We have coined this companion curve as the "Delta" curve which is represented by plotting directivity (Δ) vs the pseudo-Sommerfeld number on a linear scale. 44 Directivity itself (taken from the science of characterizing old Italian violins, which believe it or not, have many similarities to CMP tools) [45][46][47][48][49][50] is defined as the ratio of measured variances in shear force to variances of normal force at a given polishing PV condition. 44,[51][52][53][54][55] Here, the fluctuating components of shear and normal forces are the key factors and not their absolute values.…”
Section: Parametersmentioning
confidence: 99%
“…44 Directivity itself (taken from the science of characterizing old Italian violins, which believe it or not, have many similarities to CMP tools) [45][46][47][48][49][50] is defined as the ratio of measured variances in shear force to variances of normal force at a given polishing PV condition. 44,[51][52][53][54][55] Here, the fluctuating components of shear and normal forces are the key factors and not their absolute values. In this case, the ordinate and the abscissa are independent of one another, and because we use linear scales, there are no distortions or optical illusions that would have been caused by the logarithmic scales.…”
Section: Parametersmentioning
confidence: 99%
“…(12)(13)(14)(15)(16)(17) Previous work has focused on the vibrations that occur in various CMP processes. (12)(13)(14)(15)(16)(17)(18)(19)(20)(21) Fukuroda et al, Hetherington et al, Kojima et al and Rao et al studied vibrations in CMP and found that they could be used as an end-point detection technique for polishing different materials. (18)(19)(20)(21) However, the authors did not correlate the vibrations to RR.…”
Section: Introductionmentioning
confidence: 99%
“…Of the works that have studied vibrations in CMP, several have focused on Δ's role in the process. (12)(13)(14)(15)(16)(17) Philipossian et al…”
Section: Introductionmentioning
confidence: 99%